City as a Potential Source of Stress - Kuświk, Justyna (Studia Historiae Oeconomicae, 2013)
This article will present an analysis of a psychological reaction which may occur in people living in big cities, the so-called urban stress. The paper will concentrate mainly on describing the influence of strong sensory input (e.g. noise and pollution), which is characteristic of a big city, as well as social issues on the cognitive, emotional and behavioural functioning of individuals. What is more, various consequences of the emergence of stress will be discussed. The summary of the article includes conclusions drawn from a review of research and theories.